Translation of Pramoedya Ananta Toers Inem: Enhancement of Local-Global Communication - Novita Dewi (Journal of Language and Literature, 2019)
Translation of a literary work requires the balance between staying faithful to the essence of the original work while creating an artistic, unique, and distinctive piece of work in the translated language so as to evoke the same feelings and responses as the source language. Examining a number of translation strategy used in the translation of Pramoedya Ananta Toers short story Inem into English, this study shows that the translation product is to be applauded for two reasons. First, transnational translation of Prams work, that is rich in local culture, can connect and define both Indonesian and English cultures better in order to enhance global-local connectedness. Secondly, thanks to the translator, the (recreated) work becomes accessible to readers interested in learning each others language and culture.Keywords: literary translation, local cultures, global-local connectedness